2013
DOI: 10.1063/1.4824043
|View full text |Cite
|
Sign up to set email alerts
|

A novel μ-fluidic whole blood coagulation assay based on Rayleigh surface-acoustic waves as a point-of-care method to detect anticoagulants

Abstract: A universal coagulation test that reliably detects prolonged coagulation time in patients, irrespective of the anticoagulant administered, has not been available to date. An easily miniaturised, novel μ-fluidic universal coagulation test employing surface acoustic waves (SAW) is presented here. SAW was employed to instantly mix and recalcify 6 μl citrated whole blood and image correlation analysis was used to quantify clot formation kinetics. The detection of clinically relevant anticoagulant dosing with old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…A miniaturized microfluidic universal coagulation test employing surface acoustic waves detecting prolonged coagulation time in patients, irrespective of the administrated anticoagulant, has been presented by Harder and his team. 29 Recently, Eller et al 30 showed that at supratherapeutic concentrations, ACT and ROTEM analysis were influenced after administration of DOA. This ex vivo study was designed to investigate the clinical utility of already available POCT devices that are measuring global coagulation parameters such as PT or aPTT in whole blood, which can provide a simple, fast, and known method for assessment of the pharmacodynamic anticoagulant effects of DOA.…”
Section: Discussionmentioning
confidence: 98%
“…A miniaturized microfluidic universal coagulation test employing surface acoustic waves detecting prolonged coagulation time in patients, irrespective of the administrated anticoagulant, has been presented by Harder and his team. 29 Recently, Eller et al 30 showed that at supratherapeutic concentrations, ACT and ROTEM analysis were influenced after administration of DOA. This ex vivo study was designed to investigate the clinical utility of already available POCT devices that are measuring global coagulation parameters such as PT or aPTT in whole blood, which can provide a simple, fast, and known method for assessment of the pharmacodynamic anticoagulant effects of DOA.…”
Section: Discussionmentioning
confidence: 98%
“…Rivaroxaban affects INR, but INR is not used for monitoring anticoagulation . A novel μ‐fluidic universal coagulation test using surface acoustic waves has been reported to detect anticoagulation levels, including rivaroxaban and dabigatran levels, where INR cannot be used . Further studies are needed to confirm its utility, however.…”
Section: Discussionmentioning
confidence: 99%
“…The novel device uses the principle of SAW-induced mixing of sample blood with assay reagents including fluorescent microspheres. The clotting time was derived from the time taken by the rapid tumbling of the fluorescent microspheres to cease as the clot formation progresses [132]. The polymer replica of the master containing a negative relief of channels was peeled away from the silicon wafer, and the glass posts were removed.…”
Section: Indirect Machiningmentioning
confidence: 99%